PENGARUH WORK FAMILY CONFLICT, JOB INSECURITY, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN YELLOW STAR HOTEL YOGYAKARTA - Nurcahyo, Irfan Dwi; Santosa , Awan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Yellow Star Hotel Yogyakarta is one of the hotel industries in Yogyakarta that was established in 2015. The first name of Yellow Star Hotel was Hotel Seven Star, with five floors including the basement, consisting of 40 rooms in 2013. The hotel then changed management, no longer using an operator but became a combination of two hotels, namely The Groove Express Gejayan and The Groove Ambarukmo, changing its name to Yellow Star Hotel Ambarukmo and Yellow Star Hotel Gejayan at the end of 2015, precisely on December 4 and 6, 2015 with a 3-star hotel classification. Yellow Star Hotel Ambarukmo is located on Jalan Laksda Adisucipto No. 23, Depok, Sleman. While Yellow Star Hotel Gejayan is located on Jalan Affandi No. 27A, Depok, Sleman, Special Region of Yogyakarta. One of the factors that can influence turnover intention is work family conflict, job insecurity, and workload. This study aims to analyze the influence of work family conflict, job insecurity and workload on turnover intention of Yellow Star Hotel Yogyakarta employees. The data research method used uses a quantitative method approach. The sample used is a saturated sample or all employees of Yellow Star Hotel Yogyakarta totaling 70 people. The results of the study show (1) Work family conflict has a positive and significant effect on turnover intention of Yellow Star Hotel Yogyakarta employees. (2) Job insecurity has a positive and significant effect on turnover intention of Yellow Star Hotel Yogyakarta employees. (3) Workload does not have a significant effect on turnover intention of Yellow Star Hotel Yogyakarta employees.